2013
DOI: 10.1001/jamainternmed.2013.2851
|View full text |Cite
|
Sign up to set email alerts
|

Proton Pump Inhibitors and Risk of 1-Year Mortality and Rehospitalization in Older Patients Discharged From Acute Care Hospitals

Abstract: The use of proton pump inhibitors (PPIs) has rapidly increased during the past several years. However, concern remains about risks associated with their long-term use in older populations.Objective: To investigate the relationship between the use of PPIs and the risk of death or the combined end point of death or rehospitalization in older patients discharged from acute care hospitals. Design:We investigated the relationship between PPI use and study outcomes using time-dependent Cox proportional hazards regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 35 publications
4
52
1
2
Order By: Relevance
“…Recently, Kelly et al underlined how inappropriate PPI therapy is still a problem in hospitals, though it appears to be at a lower level compared with previous studies. 16,17 The present study clearly demonstrated that in over 100 years subjects the gastric acid production is preserved in 80% of the studied population. This results is quite difBref report Table 1 fering from that previously thought, and why this occurs is unknown.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, Kelly et al underlined how inappropriate PPI therapy is still a problem in hospitals, though it appears to be at a lower level compared with previous studies. 16,17 The present study clearly demonstrated that in over 100 years subjects the gastric acid production is preserved in 80% of the studied population. This results is quite difBref report Table 1 fering from that previously thought, and why this occurs is unknown.…”
Section: Discussionsupporting
confidence: 64%
“…In the USA, the use of muscle relaxants among the elderly aged over 65 years increased 136% between 1999 and 2012 34 . Proton pump inhibitors, meanwhile, elevate gastric pH, increasing the risk of infection by Clostridium difficile, bone loss, fractures, pneumonia and malabsorption 35 , and so the Beers Criteria 2015 recommends avoiding their use for more than eight weeks 9 . The medications used by the participants of the present study differed from those seen among elderly Family Health Strategy users 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Si les effets iatrogènes ont longtemps été considérés comme bénins, et le plus souvent pré-coces et transitoires, la littérature s'enrichit depuis quelques années de la description d'effets indésirables plus graves concernant majoritairement les traitements au long cours chez des personnes âgées et pouvant contribuer à réduire leur espérance de vie [5]. L'agence américaine du médicament, Food and Drug Administration (FDA), a publié en 2011 une note d'alerte sur les risques de fractures (par hypocalcémie et malabsorption de la vitamine B12) que peut engendrer un traitement trop long par IPP [6], ainsi que sur les risques engendrés par l'hypomagnésémie due à l'utilisation des IPP [7].…”
Section: Introductionunclassified